Estimación numérica en niños sordos colombianos y brasileros del 1º al 4º año de educación básica - Rios, Nohemy Marcela Bedoya (2019)
Numerical estimation is one of the basic skills that support mathematics education, but its development has been less investigated than that of the exact quantification processes, and there is very little research exploring this skill in the deaf population. This work proposes a set of three articulated studies with the purpose of analyzing some aspects of performance in numerical estimation of Colombian and Brazilian deaf students users of sign language. Each study focuses on one of the following aspects: a) representations of magnitude, b) problem-solving strategies, and c) influence of numerals in SL. The design of the three studies is comparative transnational, not experimental, with a single measure in each country. Fifty-two participants were selected, 23 in the city of Cali, Colombia, and 29 in Porto Alegre, Brazil. All students were between the 1st and the 4th year of primary education in institutions for the deaf with a bilingual educational model. In studies 1 and 2, an estimation task was used on the number line (ranges 0–10 and 0–100); in study 3, two counting tasks were presented. The results of the studies showed greater or lesser influence of each of the factors considered. In study 1, differences were found between the countries, with a tendency of Colombian students being more precise and using simple linear representations in all the grades, while the Brazilians showed advances of the precision according to the school grade and variations in the type of representations used. In study 2, a greater use of counting strategies was identified in both countries, with variations depending on the numerical context and some associations of the type of strategy with the accuracy achieved. The results of the third study showed significant differences between the countries in some numerals, which suggests that the characteristics of the numbers in SL affect performance in some quantification tasks.